The eleventh—twelfth centuries: an ʿUmān-Kīy-Kirmān/Harmuz axis? - Piacentini, Valeria Fiorani (Proceedings of the Seminar for Arabian Studies, 2013)
Echoing J.C. Wilkinson's 'Hormuz–Qalhât axis' relating to the decades between the end of the fifth to the early sixth century hijrah (eleventh-twelfth centuries AD), this paper reconsiders the political and cultural context of the southern waters of the Gulf and the western waters of the Indian Ocean, and is especially focused on the Seljuk period and the political line of Malik Qāvurd ibn Chaghrī Beg and his successors. Particularly noticeable are contemporary sources in Arabic and Persian discussing geography, chronicles, and institutional codes, such as: the Fath-nāmah-i Sind (al-Kūfī, 'Ali ibn Hamīd ibn Abī Bakr 1403/1983), Fārsnāmah (Ibn al-Balkhī 1921), Tārīkh-i Masʿūdī (Bayḥaqī 1324/1941), Tabaqat-i Nāsirī (Jūzjānī 1342-1343/1963-1964), Tārīkh-i Kirmān (Vazīrī 1339/1961), Tārīkh-i Jahān-Gushā' (Juwaynī, Ala ai-Din 1958), Tārīkh-i Wassāf (Shihāh al-Dīn, 'Abdallāh ibn Izz al-Dīn Fadl Allāh Shīrāzī [also known as al-Wassāf — the Panegirist 1852-1853]), and the 'Atabat al-Kataba (Muntajab al-Dīn Badi 'Atabeg Juwaynī 1329/1950-1951), among many others. Rereading this material, a new impression develops of the relationship of ʿUmān with the Gulf, on the one hand, and with the Indian Ocean on the other, in the period preceding the cataclysm of the Khwārizmian-Mongol invasions. Qāvurd's political line, strongly supported by his father's military campaigns and diplomatic action in central Asia, did not mark a break with the Būyids: militarization of ʿUmān, with the exception of Sūhār, annexation of the Kīj(Kič)-u-Makrān region to Kirmān, the latter representing a strategic alternative caravan route to India and to a 'great harbour-town' at the mouth of the Mihrān river, especially when sea routes were too dangerous because of piracy, Yemeni events, Fātimid competition, and Qarmatian ambitions. Under the Seljuks, the Wilāyat-i ʿUmān enjoyed a special institutional status, benefiting from a period of security and order. A new social class developed. The loyalty of Harmuz to the Seljuks was rewarded with the special status of nāhiyah under a native ruler (amīr). Harmuz became increasingly enterprising, developing a trading policy that would soon become independent in practice. By the start of the sixth (twelfth) century, Harmuz had further strengthened ties with Makrān and its harbour town (Tīz), which now became an intrinsic part of the system. A south-east Arabian trading axis grew up. Thus, with the development of Qalhāt as the port of Harmuz, Tīz/ʿUmān changed its maritime orientation. Relationships with Kirmān inside and outside the Gulf grew closer, giving life to a positive Harmuz-Kīj–ʿUmān system: a territorial block encircling a vast liquid space.